Bone-ligament-bone Cuenod grafting technique modified by Saffar-Romano for the treatment of chronic scapho-lunate dissociation - Marcuzzi, Augusto; Leigheb, Massimiliano (Acta Biomedica Atenei Parmensis, 2016)
Background and aim of the work: The authors show their experience about six patients suffering of chronic scapho-lunate (S-L) dissociation treated with the Cuenod method modified by Saffar-Romano. Methods: Clinical assessment was performed in all patients and compared before and after surgery at follow-up measuring pain value through the VAS, ROM of the wrist with a goniometer, grip strength by Jamar test, functional outcome with the Italian version of the Disability of Arm, Shoulder and Hand (DASH) score. Radiological assessment consisted in measuring S-L angle and classifying radio-carpic and inter-carpic osteoarthritis. Results: At radiographic check-up the reduction of the dissociation remained within the normal range of S-L angle (30°-60°) in 5/6 patients (83%). Clinical results were satisfactory for all the patients due to complete absence of pain and a good recovery of wrist function with more than 80% of the force and mobility compared to the contralateral side for three patients, and a recovery of more than 60% of the force and mobility for another patient. Mean DASH score was 8. All the patients returned to their previous job after a mean time of 4 months. Conclusions: Cuenod modified by Saffar-Romano grafting technique can be considered a brilliant solution for chronic S-L dissociation where S-L ligaments are completely worn included cases of SLAC I wrist.